Investigation of the Effects of Quercetin and Resveratrol Consumption on Lactic Acid Levels and Running Performance of Elite Adolescent Athletics Distance Runners - Akkaya, Büşra; Salıcı, Olcay (Progress in Nutrition, 2021)
Study Objectives: The aim of this study is to examine the effects of quercetin and resveratrol consumption on lactic acid levels and running performance of elite adolescent athletics distance runners. Methods: Four female and four male adolescent athletes who are interested in elite level athletics participated in the study and the average age of elite adolescent athletes was 16.13 ± 2.03 years, the average body weight of the athletes was 52.02 ± 6.91 kg and their average height was 168.3 ± 10.61 cm. In order to measure athletic performances; in a randomized, single-blind, crossover method used and the study lasted for 3 weeks, one week apart. They were taken to the camp on 2 determined days of each week and placebo supplements were given in the first week, 500 mg quercetin in the second week and 100 mg resveratrol in the third week. They were asked to run 1500 m without supplement on the first day of the camp. Lactic acid measurements were taken before and after the run and running times were recorded. On the second day, the same measurements were repeated with supplements. Paired - T Test was used for the analysis of the obtained data, the level of significance was accepted as 0.05. Results: According to quercetin and resveratrol interventions, only quercetin supplementation made a statistically significant difference in female elite adolescent athletes. However, although not statistically significant, there were differences in running time, which are very important for Track and Field sports. Conclusion: it can be said that this study explains quercetin supplementation decreases lactic acid levels and can provide a better performance by delaying fatigue, especially for female and relatively male athletes.